Honey In The Quran And Sunnah: Exploring Its Medicinal Properties - Klaina, Mekki (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Honey has been a subject of significant interest in Islamic culture due to its mention in the Quran and Hadith of the Prophet. The Quran describes honey as a source of healing, and the Hadith of the Prophet also speaks about its therapeutic benefits. Islamic scholars have incorporated honey into traditional medicines and written about its use in prophetic medicine. Contemporary research has increasingly focused on studying the unique properties of honey, inspired by the Quran. The approach followed in this study is descriptive and analytical. This research has shown that honey is not like other sugars and has health benefits that make it a potential cure for various diseases. However, more research is still needed to fully understand and utilize the therapeutic benefits of honey. The cooperation of researchers in prophetic medicine and specialists in modern medicine is required to further discover the benefits of honey for the treatment of various diseases, ultimately benefiting humanity. The Quran's guidance on the benefits of honey and the need for further research in this area highlight the importance of honey in Islam and its potential to contribute to human health and well-being.